Different degradation rates of nanofiber vascular grafts in small and large animal models. (22nd January 2020) - Fukunishi, Takuma; Ong, Chin Siang; Yesantharao, Pooja; Best, Cameron A.; Yi, Tai; Zhang, Huaitao; Mattson, Gunnar; Boktor, Joseph; Nelson, Kevin; Shinoka, Toshiharu; Breuer, Christopher K.; Johnson, Jed; et al.
Abstract: Nanofiber vascular grafts have been shown to create neovessels made of autologous tissue, by in vivo scaffold biodegradation over time. However, many studies on graft materials and biodegradation have been conducted in vitro or in small animal models, instead of large animal models, which demonstrate different degradation profiles. In this study, we compared the degradation profiles of nanofiber vascular grafts in a rat model and a sheep model, while controlling for the type of graft material, the duration of implantation, fabrication method, type of circulation (arterial/venous), and type of surgery (interposition graft). We found that there was significantly less remaining scaffold (i.e., faster degradation) in nanofiber vascular grafts implanted in the sheep model compared with the rat model, in both the arterial and the venous circulations, at 6 months postimplantation. In addition, there was more extracellular matrix deposition, more elastin formation, more mature collagen, and no calcification in the sheep model compared with the rat model. In conclusion, studies comparing degradation of vascular grafts in large and small animal models remain limited. For clinical translation of nanofiber vascular grafts, it is important to understand these differences.